عنوان المداخلة: الرايس حميدو أول بحار محلي في أسطول الجزائر العثمانية(1770-1815) - توتة, إسماعيل (roa, 2020)
الرايس حميدو كان شغوفا بالبحر منذ الصغر وما زاد شغفه للبحر هو تلك القصص التي كان يسمعها من البحارة أثناء عودته من الغزو. فصار متلهفا إلى سلك طريقهم ليشتغل كنوتي صغير على متن سفينة احد البحارة الذين كان عددهم كثير آنذاك في مدينة الجزائر.   وتدرج في الرتب إلى أن أصبح قائدا عاما للأسطول الجزائري سنة 1797 إلى غاية وفاته في 1815. وخلال هاته الفترة اكتسب شهرة واسعة سواءا بالجزائر أو في الأوساط الأوروبية. فقط استطاع أن يفوز في أعتى المعارك ويحصل على العديد من الغنائم والأسرى. الكلمات المفتاحية: الرايس حميدو، الأسرى، الغنائم  Abstract: Rais Hamidou was passionate about the sea since childhood, and his passion for the sea was those stories he had heard from sailors on his return from the invasion. So eager to go their way to work a little knutty on board the ship of one of the sailors, who were many at the time in the city of Algeria. He graduated in ranks until he became Commander in Chief of the Algerian fleet in 1797 until his death in 1815. During this period, he gained wide fame both in Algeria and in European circles. Only he can win the toughest battles and get many loot and captives.